Application of a hydrogel derived from porcine dermis for experimental treatment of superficial wounds - K. I. Melkonyan; Ya. A. Kozmay; T. V. Rusinova; G. P. Chuprynin; M. I. Kartashevskaya; I. I. Kartashevsky; S. V. Storozhuk; I. I. Selezneva; K. G. Gurevich (Бюллетень сибирской медицины)
Aim. To study the efficacy of dermal hydrogel application in the experimental treatment of superficial scarified wounds in rats.Materials and methods. The hydrogel was obtained from porcine dermis by alkaline hydrolysis. The DNA concentration was determined using the Nano Drop ND-1000 spectrophotometer. The study included 30 male Sphinx rats. Scarified wounds were created on the rat skin, then the rats were divided into two groups: group 1 – rats without treatment, or control group (n = 15), group 2 – rats with wound treatment with the dermal hydrogel for 5 days, or experimental group (n = 15). On day 3, 7, and 14 of the experiment, we explanted skin samples from the wound area and performed routine H&E staining.Results. On day 3 of the experiment, moderate inflammation, edema, and collagen fiber disorganization were revealed in the experimental group, and pronounced inflammation with purulent exudate was found in the control group. On day 7 of the experiment, inflammation and foci of stratified epithelium were detected in the control group. The histologic analysis of the skin samples from the experimental group showed pronounced plethora of the vessels, necrotic changes of the dermis, and edema. The total thickness of the epidermis and the thickness of its stratum corneum were greater than in the control group samples. On day 14, the differences between the groups were minimal and the epidermis was thickened in the experimental group animals.Conclusion. The study examined the effects of the dermal hydrogel on scarified wounds in rats. We found faster skin regeneration (by 1.5–2 days) in the experimental group compared to the controls. Besides, the rats of the experimental group were characterized by an increase in the number of fibroblasts in the dermis and thickened epidermis in the affected area.